Hans Kelsen’s Nomostatics and Nomodinamics Legal Theory - Arimba, Cahya Iradi (Justice Voice, 2023)
Hans Kelsen is a famous figure in the positivist school, which puts forward the concept of pure law (the pure theory of law) in the concept Hans Kelsen provides two legal theories, namely static law (nomostatics) and dynamic law (nomodinamics). The purpose of this research is to understand the two legal theories put forward by Hans Kelsen, about static and dynamic law. The method used in this research is the normative juridical method with secondary legal materials in the form of books and journals that have a relevant research focus. Nomostatics legal theory is the law as a system of norms that apply, law in its resting state while nomodynamics legal theory is the process when the law is created and applied and the law is in running condition. In using a legal theory as a basis for making a law, it is necessary to be as clear as possible about the theory in the hope that the legal theory remains relevant for the next few years so that a legal theory truly follows its purpose, namely to know legal acts and to assess these acts. A legal theory is not always perfect in terms of its relevance to the times.